Life Course Experiences, Pain and Suffering: A Case Study of an Older Mexican American Woman with Mobility Impairment - Walker, Janiece L. (2013)
There is a dearth of literature examining how adversity shapes the experiences of pain and/or suffering in a middle aged Mexican American women. The purpose of this qualitative descriptive study was to understand pain and suffering from a life course perspective as described by a Mexican American woman aging with early onset mobility impairment. This Hispanic woman experienced episodes of abuse and rejection over the life course, which may have significantly influenced her pain and suffering experience in adulthood. This adds to the literature on how adversity influences later life pain experience and provides insight on why pharmacological treatment alone may not be as successful as a holistic intervention. Hay escasez de literatura que examine cómo la adversidad da forma a las experiencias de dolor y / o sufrimiento en mujeres mexicana-americana mayores de edad. El propósito de este estudio descriptivo cualitativo fue comprender el dolor y el sufrimiento desde una perspectiva de ciclo de vida como descrito por una mujer mexicana-americana envejeciendo con inicio temprano de deterioro de movilidad. Esta Latina experimentó episodios de maltrato y rechazo, que se percibió haber afectado su experiencia de dolor y sufrimiento luego como adulta. Este estudio aumenta la literatura sobre cómo la adversidad influya la experiencia de dolor más tarde en la vida, y nos permite comprender mejor como el tratamiento farmacológico por sí solo no es tan exitoso como pueda ser una intervención integral.